Opportunities and risks of self-binding directives: A qualitative study involving stakeholders and researchers in Germany - Potthoff, Sarah; Finke, Marleen; Scholten, Matthé; Gieselmann, Astrid; Vollmann, Jochen; Gather, Jakov (Frontiers in Psychiatry, 2022)
Purpose: Self-binding directives (SBDs) are a special type of psychiatric advance directive in which mental health service users can consent in advance to involuntary hospital admission and involuntary treatment during future mental health crises. Opportunities and risks of SBDs reported by users with bipolar disorder, family members of people with bipolar disorder, professionals working with people with bipolar disorder and researchers with expertise in mental health ethics and law in the study are presented. Methods: Seventeen semi-structured interviews with users, family members and professionals, and one focus group with five researchers were conducted. The data underwent qualitative content analysis. Results: Six opportunities and five risks of SBDs were identified. The opportunities were promotion of autonomy and self-efficacy of users, relief of responsibility for family members, early intervention, reduction of (perceived) coercion, positive impact on the therapeutic relationship and enhancement of professionals’ confidence in decision-making. The risks were problems in determining and lack of mental capacity, inaccurate information or misinterpretation, increase of coercion through misuse, negative impact on the therapeutic relationship due to noncompliance with SBDs, and restricted therapeutic flexibility and less reflection on medical decision-making. Stakeholders tended to think that the opportunities of SBDs outweigh their risks given that appropriate control and monitoring mechanisms are in place, support is provided during the drafting process and the respective mental healthcare setting is sufficiently prepared to implement SBDs in practice. Conclusions: The fact that stakeholders consider SBDs as an opportunity to improve personalized crisis care for people with bipolar disorder indicates that a debate about the legal and clinical implementation of SBDs in Germany and beyond is necessary.